Putting the 'E' into LSPs : representing the environment within Local Strategic Partnerships in the UK - Lucas, K; Fuller, S (Routledge, 2005)
This article reports the findings of a qualitative study with residents living in six deprived neighbourhoods in the UK and the front-line workers and local policymakers responsible for the renewal of these areas. The study was an attempt to raise awareness of local environmental concerns in the context of a national and local policy agenda, which has, until recently, largely overlooked the impacts of degraded environments on the lives and activities of the people who live in them. A key aim for the study was to raise people's concerns with local decision-makers and examine how far these might be addressed through the existing financial, administrative and legislative arrangements for neighbourhood renewal in the UK, namely Local Strategic Partnerships. The research was designed to provide practical lessons and policy recommendations for others wishing to raise the profile of environmental justice in the context of neighbourhood level regeneration projects, in both the UK and elsewhere in the ‘developed’ world.